Harnack inequalities, a priori estimates, and sufficient statistics for nonlinear elliptic systems in quantum mechanics - Carlos C. Aranda (Electronic Journal of Differential Equations, 2012)
In this article, we consider systems of nonlinear elliptic problems and their relations with minimal sufficient statistics, which is a fundamental tool in classics statistics. This allows us to introduce new experimental tools in quantum physics.